1989
DOI: 10.1083/jcb.108.4.1431
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyclin B in meiosis I.

Abstract: Abstract. In clams, fertilization is followed by the prominent synthesis of two cyclins, A and B. During the mitotic cell cycles, the two cyclins are accumulated and then destroyed near the end of each metaphase. Newly synthesized cyclin B is complexed with a small set of other proteins, including a kinase that phosphorylates cyclin B in vitro. While both cyclins can act as general inducers of entry into M phase, the two are clearly distinguished by their amino acid sequences (70% nonidentity) and by their dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
173
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(177 citation statements)
references
References 93 publications
4
173
0
Order By: Relevance
“…The agreement of the three methods provides strong evidence that a significant fraction of the inactive Cdc2-cyclin B is not freely soluble in the cytoplasm and that at least some of this fraction is released at the activation. Our results are similar to those of Westendorf et al (1989) who described cyclin B aggregates in clam oocytes that disperse on oocyte activation, and to Beckhelling et al (2003) who found an association of Cdc2-cyclin B with annulate lamellae in frog oocytes that disperses during oocyte maturation.There are several important unresolved issues. The composition of the aggregates in starfish oocytes is not known.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The agreement of the three methods provides strong evidence that a significant fraction of the inactive Cdc2-cyclin B is not freely soluble in the cytoplasm and that at least some of this fraction is released at the activation. Our results are similar to those of Westendorf et al (1989) who described cyclin B aggregates in clam oocytes that disperse on oocyte activation, and to Beckhelling et al (2003) who found an association of Cdc2-cyclin B with annulate lamellae in frog oocytes that disperses during oocyte maturation.There are several important unresolved issues. The composition of the aggregates in starfish oocytes is not known.…”
supporting
confidence: 80%
“…There are several indications that inactive Cdc2-cyclin B is not free to diffuse in the cytosol but instead, is associated with other molecules or intracellular structures and undergoes changes in associations when it becomes activated. Among various reports, Picard and Peaucellier (1998) observed cyclin B in vesiclelike structures in starfish oocytes, Westendorf et al (1989) found evidence for cyclin B aggregates in immature clam oocytes, and Lee and Kirschner (1996) found evidence for a binding inhibitor of Cdc2-cyclin B that is associated with membranes. More recently, inactive Cdc2-cyclin B was found to be associated with annulate lamellae in immature Xenopus oocytes (Beckhelling et al, 2003).…”
mentioning
confidence: 99%
“…Homologs of cyclin proteins originally identified in clams, sea urchins, and starfish have been found in yeast, Xenopus, humans, and Drosophila (Evans et al, 1983;Swenson et al, 1986;Standart et al, 1987;Pines and Hunt, 1987;Booher and Beach, 1988;Hagan et al, 1988;Lehner and O'Farrell, 1989;Pines and Hunter, 1989;Westendorf et al, 1989;Whitfield et al, 1989). In clams, two different but highly homologous cyclins, cyclin A and cyclin B, have been identified (Evans et al, 1983;Swenson et al, 1986;Westendorf et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…One of the proteins that associates with Cdc2/Cdc28 has been identified as cyclin (Booher et al 1989;Labbe et al 1989b;Meijer et al 1989;Pines and Hunter 1989;Gautier et al 1990). Cyclins were first described in oocytes of marine invertebrates as proteins that change dramatically in abundance throughout the cell cycle, reaching maximal levels just before the onset of mitosis (Rosenthal et al 1980;Evans et al 1983;Pines and Hunt 1987;Standart et al 1987;Westendorf et al 1989). Cyclins have subsequently been identified in Drosophila Whitfield et al 1989), Xenopus (Minshull et al 1989), humans (Pines and Hunter 1989), and the fission yeast S. pombe (Booher and Beach 1988;Goebl and Byers 1988;Hagan et al 1988;Solomon et al 1988).…”
mentioning
confidence: 99%